La gestión de procedimientos administrativos y la satisfacción de los clientes en la empresa Argenper S.A. - sede Trujillo, 2019 - 2022 - Gil Gallardo, Merly Giovanna (2023)
The following Professional Sufficiency Report entitled: "The management of administrative procedures and customer satisfaction in the company Argenper S.A. - Trujillo headquarters, 2019 - 2022", sets out as main objective to describe the professional experience in terms of the management of administrative procedures and customer satisfaction in the company Argenper S.A. - Trujillo headquarters, in the position of service operator from 2019 to 2022, considering the main problems that afflict the customer service area of this organisation, as well as getting to know the company, describing the functions performed, identifying the problems in terms of the management of procedures and knowing the level of customer satisfaction, additionally, as a complementary part, proposing improvements in terms of the professional training of the student of Administration. In this regard, it is concluded that there is a certain deficiency in terms of customer service, being a Peruvian company with more than 27 years dedicated to the service of sending and delivery of money, nationally and internationally and the main services offered to the public are the sending and delivery of money, purchase and sale of foreign currency, courier and travel agency. Likewise, the main functions performed in the position of service operator are summarised in customer service, sending national and international money orders, payment of national and international money orders, sale of tickets, sending parcels, providing information in person and by telephone, as well as cash management.